IMPLEMENTASI KONSELING BEHAVIORAL DENGAN TEKNIK SELF MANAGEMENT UNTUK MENANGGULANGI PERILKU MEMBOLOS - Kadek Suhardita; I Dewa Ayu Eka Purba Dharma Tari; I Wayan Juliawan; Karolina Skolastika Wijaya (LP3M Universitas PGRI Mahadewa Indonesia, 2022)
This study aims to overcome ditching behavior through behavioral counseling with self management techniques in grade XI AP 2 students of SMK Wira Bhakti Denpasar Year 2020/2021 where the number of students targeted by the study amounted to 35 students and 5 of them had ditching behavior. Based on the evaluation results after the implementation of behavioral counseling with self management techniques in cycle I, there was a slight decrease ditching behavior in grade XI AP 2 smk Wira Bhati Denpasar Year 2020/2021 individually 74%to 68% and in groups seen an average decrease of 72.4%. After finding some weaknesses in cycle I then held improvements in cycle II so that there was a decrease in individual ditching behavior 48 % to 52 % and in groups experienced an average decrease of 48 %. Thus, it can be concluded that through the implementation of behavioral counseling with self management techniques are able to disrupt ditching behavior in grade XI AP 2 students of SMK Wira Bhakti Denpasar Year 2020/2021. Based on the results of this study, it is recommended that BK teachers should provide behavioral counseling services with self-management techniques to disrupt ditching behavior in students.